Faktor –Faktor Yang Berhubungan Dengan Hipertensi Pada Kehamilan Di Wilayah Kerja Puskesmas Padang Tepong Kecamatan Ulu Musi Kabupaten Empat Lawang - Ita Hernida; Hasanudin Nuru; Darmawansyah Darmawansyah (Gayaku Publisher, 2022)
Hypertensive disease, or high blood pressure, can lead to various health complications that endanger life while increasing the risk of heart disease, stroke, and even death. The purpose of this study was to determine the factors associated with hypertension in pregnancy in the Padang Tepong Health Centre Working Area, Ulu Musi District, Empat Lawang Regency. The method used is analytical survey research with a cross-sectional research design, with data collected in the form of primary data by distributing questionnaires to pregnant women in the Padang Tepong Health Centre Working Area, Ulu Musi District, and Empat Lawang Regency using a simple random sampling technique, as many as 56 pregnant women. Data analysis was performed using the Chi-Square test. The results of univariate analysis show that more than some mothers have a risky age during pregnancy, more than some mothers have a history of hypertension, almost as much as with less knowledge, and more than some mothers experience hypertension during pregnancy. According to the results of bivariate analysis, there is a relationship between age and hypertension in pregnancy (p = 0.034), there is a family history of hypertension with hypertension in pregnancy (p = 0.017), and there is a relationship between knowledge and hypertension in pregnancy (p = 0.009). Researchers suggest to the health centre that the results of this study can be used as additional data for the Padang Tepong health centre in handling cases of hypertension in pregnancy.